2017
DOI: 10.3991/ijet.v12i06.7008
|View full text |Cite
|
Sign up to set email alerts
|

Competency-based Approach to the Assessment of Professional Training for a Medical Student to Work with Medical Equipment

Abstract: Abstract-The article solves the problem of describing the professional training for a medical graduate in terms of competency-based approach and identification of ways to develop these qualities to work with medical equipment. A model for the competence formedness level assessment has been elaborated, which indicates all its input and output parameters.On the basis of the developed methods and algorithms for calculating the competence formedness level for the training course 'Anesthesiology, Resuscitation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
(8 reference statements)
0
9
0
1
Order By: Relevance
“…As aforementioned, the first questionnaire addressed the evaluation results of administration, training, and technical services of (CEDS). The findings of both administration and training skills are not affected by hospital size and professional role and this might be attributed, in terms of administration skills, to the great interest of MOH with managerial and administrative skills in all health facilities, while for training skills might be due to the training skills deems one of the essential characteristics for clinical engineering department staff [33][34][35]. Regarding the technical or performance skills of (CEDS), in terms of maintenance management system, there was significant difference with the hospital size and experience and this might be due to two reasons; the first is the ratio of CED engineers to technicians staff in the hospital, Fize [36] and Eisler [37] who reported that the complexity of medical equipment will decrease the need of technicians.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, the first questionnaire addressed the evaluation results of administration, training, and technical services of (CEDS). The findings of both administration and training skills are not affected by hospital size and professional role and this might be attributed, in terms of administration skills, to the great interest of MOH with managerial and administrative skills in all health facilities, while for training skills might be due to the training skills deems one of the essential characteristics for clinical engineering department staff [33][34][35]. Regarding the technical or performance skills of (CEDS), in terms of maintenance management system, there was significant difference with the hospital size and experience and this might be due to two reasons; the first is the ratio of CED engineers to technicians staff in the hospital, Fize [36] and Eisler [37] who reported that the complexity of medical equipment will decrease the need of technicians.…”
Section: Discussionmentioning
confidence: 99%
“…A competency-based approach has certain impacts on the system of knowledge assessment with a focus on students' employment prospects [15]. At the same time, the emphasis is now shifted from controlling how well particular subjects are mastered, to monitoring the development of competencies required for work [19], partly due to the fact that the level on which particular competencies are formed often depends on the student's personality [20].…”
Section: Introductionmentioning
confidence: 99%
“…He/she may be concerned with individualisation models, which are built up from various modules (general professional module, special module, independent activity module, research module, clinical experience module) [11]. Students also have the use of creativity and innovation [12,13] • Innovations: Innovative curricula design, supportive notes [14], distance learning and its impact on the quality of education [15], portfolio method [16], competencybased approach [17], responsive management system [18,19], ICTs [20][21][22] • Moral development issues: Learning progression [23], methods for fostering an ethical-deontological culture in Latin classes [24], digital games -a powerful learning environment for moral development [25] • An informal approach to teaching (museum -an informal platform for teaching) [26] In innovative education, medical students should learn by a new model of education that would fit the healthcare industry [27,28].…”
Section: Introductionmentioning
confidence: 99%